2017
DOI: 10.7554/elife.29830
|View full text |Cite
|
Sign up to set email alerts
|

The eukaryotic translation initiation factor eIF4E harnesses hyaluronan production to drive its malignant activity

Abstract: The microenvironment provides a functional substratum supporting tumour growth. Hyaluronan (HA) is a major component of this structure. While the role of HA in malignancy is well-defined, the mechanisms driving its biosynthesis in cancer are poorly understood. We show that the eukaryotic translation initiation factor eIF4E, an oncoprotein, drives HA biosynthesis. eIF4E stimulates production of enzymes that synthesize the building blocks of HA, UDP-Glucuronic acid and UDP-N-Acetyl-Glucosamine, as well as hyalur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 45 publications
1
36
0
1
Order By: Relevance
“…In the nucleus, eIF4E binds ∼3,000 capped mRNAs which typically are its export targets (36). By contrast, in the cytoplasm, eIF4E binds the majority of capped mRNAs regardless of whether eIF4E enhances their translation efficiency (28,32,(36)(37)(38). Thus, the identification of eIF4E-bound transcripts from the nucleus provides a straightforward strategy for the discovery of target RNAs.…”
Section: Results Eif4ementioning
confidence: 99%
See 1 more Smart Citation
“…In the nucleus, eIF4E binds ∼3,000 capped mRNAs which typically are its export targets (36). By contrast, in the cytoplasm, eIF4E binds the majority of capped mRNAs regardless of whether eIF4E enhances their translation efficiency (28,32,(36)(37)(38). Thus, the identification of eIF4E-bound transcripts from the nucleus provides a straightforward strategy for the discovery of target RNAs.…”
Section: Results Eif4ementioning
confidence: 99%
“…Many of the other noncoding RNAs identified are competing endogenous RNAs which act as sponges for tumor suppressive microRNAs. In parallel, many of the coding transcripts identified are similarly implicated in cancer, such as Mdm2, Myc, Mcl1, and CTNNB1 (29,32,33,37,56). Some of these RNAs play roles in the same biochemical pathways, such as CTNNB1 and the lncRNA that protects it [SLC4O1-AS1 (57)].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, RIP-Seq analysis in lymphoma cells indicated that nuclear eIF4E binds over 3000 mRNAs that encode proteins acting in lymphoma-sustaining pathways such as B-cell receptor signaling (Bcl2, Bcl6) and DNA methylation/epigenetic regulation (DNMT1, DNMT3A, HDAC1) ( Culjkovic-Kraljacic et al, 2016 ). In AML and osteosarcoma cells, eIF4E coordinately increases the export of transcripts encoding all the proteins involved in hyaluronan synthesis ( Zahreddine et al, 2017 ). Hyaluronan is a large polysaccharide with traditional roles in building the extracellular matrix, and more recently was found to encapsulate some tumor cells ( Setala et al, 1999 ; Auvinen et al, 2000 ; Kemppainen et al, 2005 ).…”
Section: The Eukaryotic Translation Initiation Factor Eif4ementioning
confidence: 99%
“…Hyaluronan is a large polysaccharide with traditional roles in building the extracellular matrix, and more recently was found to encapsulate some tumor cells ( Setala et al, 1999 ; Auvinen et al, 2000 ; Kemppainen et al, 2005 ). Indeed, Hyaluronan (HA) production was found to be required for the metastatic and invasive properties associated with eIF4E, and thus serves as the first case where this HA coat was shown to contribute to the oncogenic phenotype ( Zahreddine et al, 2017 ). Indeed, inhibition of this regulon with RNAi to eIF4E or treatment with the cap competitor ribavirin impaired the export of the RNAs encoding the HA machinery, reduced HA production and decreased the invasive and metastatic activities of these cells.…”
Section: The Eukaryotic Translation Initiation Factor Eif4ementioning
confidence: 99%
See 1 more Smart Citation